Functional annotation of putative conserved proteins from Borrelia burgdorferi to find potential drug targets. (2016) - Khan, Shama; Jamal, Mohammad Sarwar; Anjum, Farah; Rasool, Mahmood; Ansari, Abulaish; Islam, Asimul; Ahmad, Faizan; Hassan, Md. Imtaiyaz
The spirochete Borrelia burgdorferi is causative agent of Lyme disease. We have used various bioinformatics tools for predicting the function of unknown proteins present in B. burgdorferi's genome. While analysing the proteome data of B. burgdorferi, we have found 819 proteins. Out of these, 241 proteins are conserved hypothetical proteins (HPs), i.e., proteins of unspecified structures and biochemical functions. We have successfully annotated 120 HPs, and their corresponding functions have been predicted using different tools. On the basis of predicted functions, we have divided them into functional classes. Annotation and identification of functionally important regions in HPs from B. burgdorferi will enhance our understanding of new functional proteins, virulence mechanism and adaptability in host system.